Concepções da atividade física: perspectivas para o fortalecimento da Nação - da Silva, Eliazar Joao [UNESP] (Pontifícia Universidade Católica do Rio Grande do Sul (PUC-RS), 2007)
From the 1930's, particularly during World War II, some different phenomena rise as alternatives to strengthen the people's physical, especially in countries like Germany and Italy. Keeping different proportions, that phenomenon was seen in Brazil through a policy to increase the value of the physical activities, mainly during the Estado Novo. This article tries to analyze that policy.
Ideas about physical activity: views on strengthening a nation (World War II)
Keywords: nation; physical education; politics